ChemInform Abstract: Design of Hybrid Heterocyclic Systems with a Furoxanylpyridine Core via Tandem hetero‐Diels—Alder/retro‐Diels—Alder Reactions of (1, 2, 4‐Triazin‐3‐yl)furoxans. Issue 33 (27th July 2016) - Fershtat, Leonid L.; Larin, Alexander A.; Epishina, Margarita A.; Ovchinnikov, Igor V.; Kulikov, Alexander S.; Ananyev, Ivan V.; Makhova, Nina N.
Abstract: The title methods involve the [4+2] cycloaddition of enamine or norbornadiene to the triazine ring of triazinfuroxans followed by one‐pot transformation of the formed intermediates affording a series of polyheterocyclic compounds combining furoxan and pyridine rings in one molecule through a C—C bond.